2001
DOI: 10.1185/030079901750120187
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention of Breast Cancer: An Overview

Abstract: The role of lifestyle modifications, antioestrogens, cyclo-oxygenase-2 inhibitors and prophylactic mastectomy in reducing breast cancer is reviewed. It is concluded that avoiding postmenopausal obesity and regular physical activity are simple measures that seem to reduce breast cancer risk. There is no conclusive evidence that dietary modification and vitamin supplementation significantly reduce the risk of breast cancer. The evidence suggests that tamoxifen significantly reduces the risk of breast cancer in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…TAM presently represents the most efficacious prophylactic therapy for women at high risk of developing hormone-dependent breast cancer [13,14]. While it primarily acts as an antiestrogen, TAM also exerts estrogenic effects on various tissues, including bone and the reproductive tract [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TAM presently represents the most efficacious prophylactic therapy for women at high risk of developing hormone-dependent breast cancer [13,14]. While it primarily acts as an antiestrogen, TAM also exerts estrogenic effects on various tissues, including bone and the reproductive tract [13].…”
Section: Discussionmentioning
confidence: 99%
“…TAM is currently the most commonly used first-line therapy for the treatment of hormone-dependent breast cancer [13][14][15] and has substantial potential as a prophylactic treatment for women with an elevated risk of developing breast cancer [16]. TAM reduces the proliferation of normal and neoplastic rodent and human breast cells by several mechanisms that lead to apoptosis [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…1 Genetic testing has identified women carrying an 85% lifetime predisposition to breast adenocarcinoma. 2 To reduce the incidence of malignancy, prophylactic mastectomy has been proposed.…”
mentioning
confidence: 99%
“…We previously reviewed the literature regarding the prevention of breast cancer 1 , and concluded that specific lifestyle modifications (regular exercise, reduced alcohol intake, avoidance of postmenopausal obesity), tamoxifen and prophylactic mastectomy were associated with a significant reduction in breast cancer risk. We also discussed the conflicting results and controversies regarding tamoxifen as a chemopreventative agent.…”
Section: Introductionmentioning
confidence: 99%